Risk factors for urinary incontinence in institutionalized elderly (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: To analyze the risk factors for urinary incontinence (UI) in institutionalized elderly. Methods: Cross-sectional, analytical, documentary study done by collection in 203 medical records of a long-stay institution in northeastern Brazil. An instrument for sociodemographic and health characterization and the values of the Mini Mental State Examination (MMSE) were used. The data were analyzed from the descriptive, inferential and multiple logistic regression. Results: The prevalence of UI was 42.36% and higher in women (66.28%), older (mean: 79.62 years) and dependent (89.53%). There was an association between age (p = 0.01), sex (p = 0.024), marital status (p = 0.007), religion (p = 0.015), with whom resided before institutionalization (p = 0.033), degree of dependency (p < 0.001), MMSE values (p < 0.001) and cardiovascular (p < 0.001) and neurological diseases (p < 0,001). The risk factors for UI were number of diseases (OR = 1.17; 95% CI = 1.02-1.34), consumption of five to nine medications (OR = 4.07, 95% CI = 1.14-14.52), single (OR = 2.09, 95% CI = 1.30-8.01), dependent (OR = 3.27, 95% CI = 1.33-8.04) and had a low MMSE score (OR = 0.88, 95% CI= 0.85-0.93). Conclusion: The results reveal the importance of studying UI in this population to identify early risk factors that can be prevented.